(untitled) (LACCEI, 2024)
This work introduces an easy-to-fabricate, versatile, and affordable mechanisms kit developed as complementary material for mechanical engineering courses. This kit allows easy physical assembly of different mechanisms that enable deeper comprehension of mechanical concepts, validation of results, and easy visualization of mechanisms through an iterative, exploratory, and reflective process. The kit contains an acrylic base with perforations, acrylic and 3D printed mechanical components, M3 screws, and measuring elements. Its design is based on the hands-on learning approach proposed by constructivist Jean Piaget and principles of the didactic materials introduced by Maria Montessori. The article presents a detailed description of the kit and implementation examples.